Effect of Moisture Content on Some Physical and Mechanical Properties of 'Genjah Arum' Local Rice (Oryza sativa L) Variety in Banyuwangi. Issue 1 (June 2020) - Sandra,; Putri, R E; Djoyowasito, G; Wijaya, S N
Abstract: Designing post-harvest rice equipment and machinery requires data on its physical and mechanical properties. Physical and mechanical properties were examined in the local variety rice 'Genjah Arum' with a moisture content of 12.80%, 15.90% and 20.50% (wet basis). The physical properties measured are axial diameter and average diameter, where the higher the moisture contents the diameter increases. Sphericity, volume, and surface area, will increase if the moisture content is higher. If the moisture content rises, the average thousand grain weight will increase. There is an increase in true density and bulk density with increasing moisture content. Porosity decreases with the addition of paddy moisture content. Mechanical properties at moisture content of 12.80%, 15.90% and 20.50% are 9.12 kgf, 7.162 kgf and 6, 196 kgf. The static angle of friction is measured on glass, plywood and stainless steel, the highest friction angle measurement results found on plywood.